Mineral chemistry and thermobarometry of Eocene alkaline volcanic rocks in SW Germi, NW Iran - Mobashergermi, Mohammad; Zarei Sahamieh, Reza; Aghazadeh, Mehraj; Ahmadikhalaj, Ahmad; Ahmadzadeh, Gholamreza (Iranian Journal of Earth Sciences, 2018)
Petrography and chemistry of minerals showing that Eocene alkaline volcanic rocks in southwestern of Germi (Talesh zone, NW Iran) mostly have basaltic composition. Mineralogically these rocks are composed of diopsidic clinopyroxene and labradoritic plagioclase phenocrysts. The microlithic and glassy groundmass composed of sanidine, clinopyroxene, biotite, pargasitic amphibole and magnetite associated with devitrified glass. Clinopyroxenes show relatively high Mg-numbers (0.76-0.93), low AlVI (mostly <0.1), suggesting relatively low-pressure ( 5), and water content 2.5 to less than 10% and high oxygen fugacity (-8.38-11.51) of crystallization condition. High amount existence of magnetite coexisting with amphibole and biotite mineral confirm high fugacity of the host magma. According to clinopyroxene and feldspar thermometry, estimated crystallization temperature varies between 1106˚C to 1200 ˚C. The clinopyroxene and amphibole mineral composition of studied rocks indicate that they have been formed in a back-arc basin environment. Mineral chemistry in the current zone shows that composition and genesis of common minerals these magmatic rocks are similar to Pushtasar basaltic rocks in the northern part of this area.